Comparison of N2O Emissions From Cold Waterlogged and Normal Paddy Fields - Xu, Xiangyu; Zhang, Minmin; Xiong, Yousheng; Shaaban, Muhammad; Yuan, Jiafu; Hu, Ronggui (Frontiers in Environmental Science, 2021)
Paddy fields are major sources of atmospheric N2O. Soil temperature and moisture strongly affect N2O emissions from rice fields. However, N2O emissions from cold-waterlogged paddy fields (CW), an important kind of paddy soil in China, is not well studied so far. It is not clear whether the N2O emissions from cold-waterlogged paddy fields are the same as normal paddy fields (NW). We investigated the N2O emissions characteristics from the normal paddy field (NW) and cold waterlogged paddy field (CW) under with (R1) and without (R0) rice; compared the difference and influencing factors between the CW and NW paddy fields at two sites in South China. The results showed that the N2O cumulative emissions were 4.1±6.0 and 9.3±8.8 mg m-2 from the CWR1 in YX site and DY site, were 10.9±6.9 and 18.5±8.8 mg m-2 from the CWR0 in YX site and DY site, were 42.4±19.5 and 158.7±101.7 mg m-2 from the NWR1 in YX site and DY site, were 10.9±6.9 and 18.5±8.8 mg m-2 from NWR0 in YX site and DY site, respectively. The structural equation models (SEMs) showed that the N2O emissions are mainly driven by rice planting and soil moisture in the NW paddy fields at the annual scale, while by soil temperature in the CW fields. Overall, N2O emissions from cold waterlogged paddy fields are significantly lower than those of normal rice fields due to the low temperature and higher water content; there may also be complete denitrification that may lead to a decrease in N2O emissions.